Rapunzel syndrome's silent cry: addressing neglect and psychiatric factors in pediatric cases - Arshia Warsi; Rabeea Mushtaq; Syed Waqas Ali; Farah Anwer (SpringerOpen, 2024)
Abstract Introduction Rapunzel syndrome is a very rare form of trichobezoar. It is strongly linked to psychiatric conditions; trichotillomania and trichophagia. These conditions in the pediatric population point to the presence of childhood stressors like child neglect, abuse, etc. This case report highlights that child neglect may be an underlying contributing factor in selected cases of Rapunzel syndrome. Hence, a multidisciplinary approach should be sought in all cases of Rapunzel syndrome, catering to the emotional and psychological needs of the pediatric population. Case presentation A 7-year-old girl from a low socioeconomic background presented with periorbital and facial swelling, abdominal distension, and pallor. On physical examination, she showed bilateral pitting edema and a distended abdomen with poor overall hygienic condition. Her family history was positive for Wilson's disease. Lab investigations highlighted iron deficiency anemia (Hb 8.2 g/dL), with normal liver function. Ultrasound demonstrated ascites, liver changes, and pleural effusion. The work-up for Wilson's disease was unremarkable. During the hospital course, her abdominal distention lessened; a non-tender epigastric mass (4 × 5 cm) was thus discovered. An abdominal X-ray revealed an entangled mass outlining the gastric shadow. Her parents also revealed a history of trichophagia. Suspecting a large trichobezoar, a laparotomy was performed. After the midline incision, the stomach was opened anteriorly between stay sutures along the curvature. It delivered a large trichobezoar, 65 cm in length extending up to the proximal jejunum. Rapunzel syndrome diagnosis was finally established. Conclusion This unique presentation emphasizes the need to consider this rare etiology, even with unusual clinical histories especially with a history of child neglect, while collaborative surgical interventions facilitate successful outcomes.